Entry and Exit Strategies in Migration Dynamics - Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2006)
This work is devoted to study the role of combined entry and exit strategies in the migration process. We develop a real option model in which the community of immigrants in the host country is described as a club and the immigrants benefits is a U-shaped function, depending on the dimension of the district. There exist two threshold levels: the first one triggers the migration choice, while the second triggers the return to the country of origin. The theoretical results show that the phenomenon of hysteresis is amplified by the existence of a community both in the entry case and in the exit case. Furthermore, the community can reduce the minimum wage level required to trigger both exit and entry: this fact could explain why in some cases we observe migration inflows with a low wage differential and also with underunemployment. We show also some possible further extensions of the model: in one case we introduce a possible way to select the entrants skills and in another case we show some theoretical implementations to include possible policy shocks in the migrants choice.
Keywords: F22; H49; O15; R23; 330; Migration; Real Option; Theory of Clubs; Network Effect